The image of Polish family in the Internet – semiotic analysis of selected family forums - Kaczmarzyk, Małgorzata Anna; Zbierzchowska, Alicja (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2016)
To many people media are a natural source of knowledge these days. One such communication medium can be a discussion forum, which will be put to analysis in this paper. Yet, each message contains a meaning confined within a specific ideology conveyed by discourse used by participants of a given forum. It is this discourse that may contribute to introduction of an educational model significant to a given family. Through acquisition as well as the construction of meanings, forum members build a bond and believe in the values and educational model professed by them. Whether,however, family forums prove to be related to discourse conveying a given ideology and their communication potential proves to constitute an information network will be shown in this paper in the course of an analysis of selected discussion forums.
Keywords: media; family forums; discourse; ideology; communication potential